Nachhaltigkeitsindikatoren und Partizipation - Wittek, Susanne; Feindt, Peter H.; Gessenharter, Wolfgang; Hoppe, Jutta; Seifert, Eberhard K. (Hamburg University Press, 2002)
The workshop documentation was developed as part of the inter-university project "Participatory development of indicators of sustainability. A contribution to a process-oriented sustainability strategy ". It was carried out at the beginning of March 2000 to April 2001 by scientists from the University of Hamburg, the Hamburg University of Economics and Politics (Hochschule für Wirtschaft und Politik, HWP), the University of the Federal Armed Forces Hamburg (Universität der Bundeswehr) and the Wuppertal Institute for Climate, Environment and Energy (Wuppertal Institut für Klima, Umwelt, Energie). The workshop documented here took place on March 23, 2001 at the University of the German Armed Forces. The project team presented its work results to an audience from science and practice for discussion. Participants included representatives from companies, government departments at state and municipal level, educational institutions, consulting companies, statistical offices and associations, universities and research institutions from social, engineering and natural sciences disciplines. They came from Hamburg, Schleswig-Holstein, Lower Saxony and Baden-Württemberg. The documentation contains the lectures of four project participants, in which central results of the project are presented, and corrections by external scientists and experts. A summary of the discussion follows.